(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This study seeks to evaluate the strategic performance using the balanced scorecard based on real data, for the Al-Kindi company for the production of veterinary vaccines listed in the Iraq Stock Exchange, the research sample, because these costs affect administrative decisions, and the purpose of applying the scorecard to evaluate strategic performance is effectiveness and importance The balanced scorecard in evaluating the strategic performance of the Iraqi industrial companies, indicating the importance of formulating the environmental dimension and the social dimension within the strategic dimensions of the balanced scorecard. It is clear from what has been presented in this research the reliance on the scorecard axes in evaluating the strategic performance, as most of the indicators of the scorecard axes were towards improving the ability of management performance when choosing decisions from among the available decisions. Enabling the administration to set annual budgets in a way that touches the economic reality without exaggeration or unfairness in estimating future returns. This study recommends the importance of applying one of the methods of evaluating the strategic performance in order to make the right decisions and the crisis at the right time, specifically the balanced performance card.